2017
DOI: 10.1074/mcp.m116.065904
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Approach Identifies Vpr Binding Protein as Novel Host Factor Supporting Influenza A Virus Infections in Human Cells

Abstract: Influenza A virus (IAV) infections are a major cause for respiratory disease in humans, which affects all age groups and contributes substantially to global morbidity and mortality. IAV have a large natural host reservoir in avian species. However, many avian IAV strains lack adaptation to other hosts and hardly propagate in humans. While seasonal or pandemic IAV strains replicate efficiently in permissive human cells, many avian IAV cause abortive nonproductive infections in these hosts despite successful cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 79 publications
(69 reference statements)
0
25
0
Order By: Relevance
“…However, it is critical to also emphasize that this is not the only relevant factor for IAV host range. For example, despite the overall similar host response, we and others have previously described host factors affecting human and avian virus infections [20][21][22][23]25,32 . It is also well-established that the RdRp of avian-adapted strains is less active in human cells 8,9 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, it is critical to also emphasize that this is not the only relevant factor for IAV host range. For example, despite the overall similar host response, we and others have previously described host factors affecting human and avian virus infections [20][21][22][23]25,32 . It is also well-established that the RdRp of avian-adapted strains is less active in human cells 8,9 .…”
Section: Discussionmentioning
confidence: 79%
“…While the avian virus is not adapted to efficient growth in cultured human cells and causes a nonpermissive infection, the seasonal human virus replicates efficiently. We demonstrated previously that the Pan virus produces >1,000 fold more infectious viral progeny than the non-adapted virus, even though both strains efficiently enter human cells and initiate their gene expression program 32 .…”
Section: Quantifying the Dynamic Proteome Of Permissive And Non-permimentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, global MS-based proteomics studies were performed to identify such factors. These analyses focused either on the identification and characterization of host-virus protein interactions ( 9 , 10 ), or on the analyses of IAV-induced changes in host protein abundances ( 11 13 ). In the current study, we aimed to characterize comprehensively IAV-induced changes in the host cell proteome and to study the influence of different cell lines on the observed effects.…”
mentioning
confidence: 99%
“…The A549 human lung adenocarcinoma epithelial cell line and the Calu-3, a human bronchial epithelial cell line, have been widely used to study influenza virus-host interactions [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78], viral protein biochemistry [79,80], drug studies [81][82][83] and for performing large-scale screens, such as a CRISPR activation screen, to identify genes that inhibit influenza virus infection when they are overexpressed [82].…”
Section: Immortalized Lung Cells Eg A549 and Calu-3mentioning
confidence: 99%